Law and development and the global discourses of legal transfers (Cambridge studies in law and society, 2012)
This volume of essays contributes to the understanding of global law reform by questioning the assumption in law and development theory that laws fail to transfer because of shortcomings in project design and implementation. It brings together leading scholars who demonstrate that a synthesis of law and development, comparative law and regulatory perspectives (disciplines which to date have remained intellectually isolated from each other) can produce a more nuanced understanding about development failures. Arguing for a refocusing of the analysis onto the social demand for legal transfers, and drawing on empirically rich case studies, contributors explore what recipients in developing countries think about global legal reforms. This analytical focus generates insights into how key actors in developing countries understand global law reforms and how to better predict how legal reforms are likely to play out in recipient countries"--